2013
DOI: 10.1080/19476337.2012.727033
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical quality of tequila during barrel maturation. A preliminary study

Abstract: Physicochemical quality of tequila during barrel maturation. A preliminary study Calidad fisicoquímica del tequila durante su maduración en barrica. Un estudio preliminar Silver Tequila 100% agave was aged in new oak barrels from four French regions. The evolution of physicochemical parameters regulated by Official Mexican Standard, as well as color, turbidity, total acidity and pH were assayed during 34 weeks of maturation. Analysis of variance (ANOVA) showed significant differences between barrel origin on f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…For taxation and production regulation, alcoholic beverages are divided into three general classes: beers, wines, and spirits (or distilled beverage). Ageing is one of the most important operations in the traditional technology of manufacturing high-quality spirits (López-Ramírez, Martín-del-Campo, Escalona-Buendía, García-Fajardo, & Estarrón-Espinosa, 2013;Mosedale & Puech, 1998). Many aspects of spirits, such as flavor development in whiskey maturation, are studied during the ageing period (Piggott, Conner, & Paterson, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…For taxation and production regulation, alcoholic beverages are divided into three general classes: beers, wines, and spirits (or distilled beverage). Ageing is one of the most important operations in the traditional technology of manufacturing high-quality spirits (López-Ramírez, Martín-del-Campo, Escalona-Buendía, García-Fajardo, & Estarrón-Espinosa, 2013;Mosedale & Puech, 1998). Many aspects of spirits, such as flavor development in whiskey maturation, are studied during the ageing period (Piggott, Conner, & Paterson, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In general, the color of grape juice and wine is an important attribute that is related to the visual appeal and quality and that is attributed to the free anthocyanins, principally as flavylium cation (red) and quinoidal anhydro-base (blue), anthocyanin self-association and copigmentation of anthocyanins with other phenols in wines. In addition, the content of tartaric esters is 60 mg/L, which is significantly lower than the content of 250 mg/L in grape wines; this result may be explained by the lower tartaric acid content in Semen Astragali Complanati and by the yeast strain and the conditions that were used for fermentation (López-Ramírez, Martín-del-Campo, Escalona-Buendí, García-Fajardo, & Estarrón-Espinosa, 2013;Zhang et al, 2016). The concentration and relative distribution of ester are usually influenced by the yeast variety and fermentation parameters, such as pH, temperature, oxygen levels, fatty acid or sterol levels (Sudheer Kumar, Varakumar, & Reddy, 2012).…”
Section: Physicochemical Characteristics Of the Semen Astragali Complmentioning
confidence: 81%
“…Prior studies of the chemical mechanisms involved in the maturation of whisky showed that the formation of acetaldehyde, acetic acid and ethyl acetate originates in the distillate, whilst some acetic acid is produced by interactions between the distillate and wood components . Furthermore, López‐Ramírez et al described physicochemical changes that arise as a consequence of tequila barrel maturation; among the parameters evaluated they observed a considerable increase in higher alcohols, methanol, ester, acetaldehyde and furan‐2‐carboxaldehyde (furfural) content in the first weeks of maturation, thereby confirming the influence of the aging process on tequila flavour. The current results are in accordance with these findings, since increases in the concentrations of these major compounds were observed in the matured tequila (Table ).…”
Section: Resultsmentioning
confidence: 99%